Diversification dynamics of mammalian clades during the K–Pg mass extinction. (30th September 2018) - Pires, Mathias M.; Rankin, Brian D.; Silvestro, Daniele; Quental, Tiago B.
Abstract : The Cretaceous/Palaeogene (K–Pg) episode is an iconic mass extinction, in which the diversity of numerous clades abruptly declined. However, the responses of individual clades to mass extinctions may be more idiosyncratic than previously understood. Here, we examine the diversification dynamics of the three major mammalian clades in North America across the K–Pg. Our results show that these clades responded in dramatically contrasting ways to the K–Pg event. Metatherians underwent a sudden rise in extinction rates shortly after the K–Pg, whereas declining origination rates first halted diversification and later drove the loss of diversity in multituberculates. Eutherians experienced high taxonomic turnover near the boundary, with peaks in both origination and extinction rates. These findings indicate that the effects of geological episodes on diversity are context dependent and that mass extinctions can affect the diversification of clades by independently altering the extinction regime, the origination regime or both.